Description of Parenting Self-Efficacy in Mothers with Infants Age 0-6 Months at Panti Village, Panti District, Jember Regency - Aprinia Fajar Sukmawati; Latifa Aini Susumaningrum; Kholid Rosyidi Muhammad Nur (Pustaka Kesehatan, 2023)
Infancy (0-6 months) is a golden period as well as a critical period because at this time a process of rapid growth and development occurs and requires a lot of care and precision in the parenting process. One of the factors that can affect the care of infants is parenting self-efficacy. Parenting self-efficacy is a central cognitive element in parenting competence in the form of beliefs that refer to feelings in their role as parents or perceptions of parents' abilities to have a positive influence on children's behavior and development.This research was to identify the description of parenting self-efficacy in mothers of infants aged 0-6 months. The research design was an analytical descriptive research. The technique of collecting data performed was total sampling by taking 90 mother respondents of infants aged 0-6 months. Data were collected using a PMP S-E and MSPSS questionnaire. The results of the study shows that mothers who have infants aged 0-6 months in Panti Village, Panti District, Jember Regency have high parenting self-efficacy as many as 76 people (84.4%). This shows that mothers have high confidence in their ability to provide care for their infants.